The Translation Analysis of Logical Metaphors in Leveling Books for Children - Kusuma Putri, Devanni; Nababan, MR.; Wiratno, Tri (Universitas Muhammadiyah Semarang, 2024)
This descriptive-qualitative research investigates the use of logical metaphors in children's book translations published by the Agency for Language Development and Cultivation. These translations are categorized into four reading levels: Pembaca Awal (Early Level), Pembaca Semenjana (Intermediate Level), and Pembaca Madya (Upper-intermediate Level).Due to the inherent differences in difficulty among these levels, the research examines translation techniques, shifts, and the quality in terms of accuracy and acceptability. To ensure trustworthiness, the study employs triangulation through various data-collecting methods and source data selection. These methods include document analysis and focus group discussions (FGD) with three raters. Additionally, domain, taxonomy, componential, and cultural-theme analysis were used to analyze the data.The results indicate that the most commonly used technique, established equivalent, maintains the logical metaphors without shifting them, leading to positive effects on accuracy and acceptability. Similarly, implicitation, paraphrase, compensation, and transposition techniques also contribute positively, although they are less frequently used. In contrast, other less common techniques such as discursive creation and deletion, shift both the logical meaning, resulting in decreased accuracy and acceptability.